Inculcation of moral values in fieldwork approaches to local study students' perception. - Salleh, Mohamad Johdi; Hussien, Suhailah (International Islamic University Malaysia, 2011)
This paper discusses a study on the fundamental aspect of local study in the school curriculum, with reference to the fieldwork approaches in the learning of history and geography, Integrated Curriculum for Secondary School (ICSS) Malaysia. The focus is discussion on the aim, objectives and nature of fieldwork approaches to local study related to the inculcation of moral values as stipulated in the Philosophy of Education, Malaysia. The study involved eight hundred students of Lower Secondary level from the selected schools particularly in the states of Perak and Terengganu. Instruments used were questionnaire and interviews of the selected respondents. The findings of the study were presented in frequency, percentage and analysis of the interviews. The finding of the study shows that there were various perceptions of moral values in the fieldwork of local study.